A thermogravimetric analizer for corrosive atmospheres and its application to the chlorination of ZrO2-C mixtures - Pasquevich, Daniel M.; Caneiro, Alberto (Comisión Nacional de Energía Atómica; Argentina)
Fil: Pasquevich, Daniel M. Comisión Nacional de Energía Atómica; Argentina